Reverse-biform game based resource sharing scheme for wireless body area networks. (25th July 2019) - Kim, Sungwook
Current advances in wireless sensor technologies have contributed to the development of wireless body area network (WBAN). Due to specific features and reliability requirements in WBAN, a number of new challenges have been introduced to design novel WBAN protocols. In order to cope with these challenges, game theoretic approach can allow WBANs to improve their performance while increasing their flexibility and adaptability. In this paper, we develop a new WBAN resource sharing scheme based on the reverse-biform game model. Based on the dual-level phases, the limited WBAN resource is effectively shared by employing a game manner. The simulation results demonstrate that our game-theoretic framework can provide the ability to practically respond to current WBSN conditions. This approach is suitable for real WBAN operations, particularly for the energy efficiency, network throughput, and quality of service (QoS) provisioning.